The Gut Microbiota Activates AhR Through the Tryptophan Metabolite Kyn to Mediate Renal Cell Carcinoma Metastasis - Dai, Guoyu; Chen, Xiang; He, Yao (Frontiers in Nutrition, 2021)
Background: The incidence of renal cell carcinoma (RCC) is increasing year by year. It is difficult to have complete treatment so far. Studies have shown that tryptophan metabolite Kynurenine (Kyn) affects cell proliferation, migration, apoptosis, adhesion, and differentiation. Our aim is to explore whether Kyn activates aromatic hydrocarbon receptor (AhR) to mediate RCC metastasis. Methods: We collected RCC tissues and feces from RCC patients. 16S rRNA technology was performed to analyze the gut microbial composition of RCC patients. LC-MS/MS was used to analyze the gut microbial metabolites. The AhR was inhibited and treated with Kyn. Immunofluorescence was used to measure the degree of AhR activation. The migration and invasion ability of 786-O cells was tested by Transwell assay. Flow cytometry and cell cycle assay were utilized to observe the apoptosis and cycle of 786-O cells. CCK-8 assay was used to detect 786-O cells proliferation. qRT-PCR and Western blot were used to detect AhR and EMT-related genes expression level. Results: AhR expression was up-regulated in RCC tissues. RCC gut microbiota was disordered. The proportion of Kyn was increased in RCC. After being treated with Kyn, the migration, invasion, and proliferation ability of 786-O cells were decreased. Furthermore, the expression of EMT-related protein E-cadherin decreased, and the expression of N-cadherin and Vimentin increased. The proportion of 786-O cells in the S phase increased. The apoptosis rate of 786-O cells was inhibited. Conclusion: The tryptophan metabolite Kyn could activate AhR. Kyn could promote 786-O cells migration and invasion. Gut microbiota could activate AhR through its tryptophan metabolite Kyn to mediate RCC metastasis.